2021
DOI: 10.1038/s41598-021-86019-2
|View full text |Cite
|
Sign up to set email alerts
|

Low cardiac dose and neutrophil-to-lymphocyte ratio predict overall survival in inoperable esophageal squamous cell cancer patients after chemoradiotherapy

Abstract: We aimed to determine the prognostic significance of cardiac dose and hematological immunity parameters in esophageal cancer patients after concurrent chemoradiotherapy (CCRT). During 2010–2015, we identified 101 newly diagnosed esophageal squamous cell cancer patients who had completed definitive CCRT. Patients' clinical, dosimetric, and hematological data, including absolute neutrophil count, absolute lymphocyte count, and neutrophil-to-lymphocyte ratio (NLR), at baseline, during, and post-CCRT were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
(22 reference statements)
2
8
0
Order By: Relevance
“…We first compared the 10 patients whose disease progressed with the 74 other patients who underwent surgery, and the multivariate logistic analysis demonstrated that the length of the lesion, the NLR before nCRT, and the amount of change in haemoglobin were independent predictors of PD. This is consistent with most previous studies, indicating that a high NLR is indeed an adverse factor for nCRT ( 12 , 13 , 16 , 29 ). Then, we turned our attention to the pCR group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We first compared the 10 patients whose disease progressed with the 74 other patients who underwent surgery, and the multivariate logistic analysis demonstrated that the length of the lesion, the NLR before nCRT, and the amount of change in haemoglobin were independent predictors of PD. This is consistent with most previous studies, indicating that a high NLR is indeed an adverse factor for nCRT ( 12 , 13 , 16 , 29 ). Then, we turned our attention to the pCR group.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, researchers have been looking for new predictors for the efficacy of nCRT. The NLR is an indicator of inflammation that has been linked with the prognosis of oesophageal cancer and other tumours in many studies (9)(10)(11)(12)(13)(14)(15)(16). Sun Yat-sen University Cancer Center retrospectively analysed 306 ESCC patients who underwent nCRT and found that the NLR before nCRT and the PLR after nCRT were independent predictors of pCR (17).…”
Section: Introductionmentioning
confidence: 99%
“…This observation can be of major clinical importance in view of key roles for neutrophils in CVD ( 34 ) and a recent report on a link between the severity of aortic stenosis and NETosis ( 35 ). Furthermore, the neutrophil-to-lymphocyte ratio has been associated with worse patient survival after chemoradiotherapy ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol-rich diet modified the expression of 1.102 (898 unique human orthologs) genes in the aorta, 612 (492) genes in the aortic valve, 281 (229) genes in the mitral valve, and only 4 (3) and 6 (6) genes in the tricuspid and pulmonary valve, respectively. The lard-rich diet yielded much less DEGs than the cholesterol-rich diet, comprising 76 (66) genes in the aorta and 40 (36) genes in the aortic valve. No DEGs were found in the three other cardiac valves in response to the lard diet.…”
Section: Differential Rna Expression Profiles In the Aorta Aortic Val...mentioning
confidence: 99%
“…In addition, NLR was also reported as a meaningful predictor of outcome in patients with extensive small-cell lung cancer who received radiation treatment ( 26 ). It was reported that radiotherapy also reduced the level of NLR, which may contribute to a longer survival time, even in patients with advanced or metastatic disease ( 27 ). Although the above clinical evidence reported a meaningful predictive value of NLR/LMR/PLR in practice, few basic experiments were conducted to investigate the intrinsic mechanism for the phenomenon.…”
Section: Discussionmentioning
confidence: 99%